Physics for you - Johnson, Keith (Stanley Thornes (Publishers) Ltd, 1996)
To accommodate the latest National Curriculum requirements this physics textbook has new pages and extra questions added. The book contains a character called Professor Messer who is always making mistakes and students are invited to put him right.